Hemodynamic Response to Acute Volume Load and Endomyocardial NO-synthase Gene Expression in Heart Transplant Recipients. Issue 6 (26th May 2022) - Kobediona, Monika; Bartunek, Jozef; Delrue, Leen; Van Durme, Frederik; Lau, Chirik Wah; Moya, Ana; Verstreken, Sofie; Heggermont, Ward; Dierckx, Riet; Goethals, Marc; Vanderheyden, Marc
Abstract : Background: A pulmonary capillary wedge pressure (PCWP) >18 mm Hg following volume load has been proposed as a partition value for the detection of heart failure with preserved ejection fraction. As hemodynamic changes in filling pressures (FP) have been attributed to a nitric oxide (NO)-mediated rightward shift of the pressure-volume relationship, we investigated the hemodynamic response to volume load in heart transplant recipients (HTx) and examined the role of inducible NO synthase (iNOS) gene expression on diastolic function changes. Methods: In 36 HTx, FPs were measured before and after volume load, following which Starling curves were constructed using PCWP and cardiac index (CI). Patients were categorized into those with normal (group A, n = 21) and abnormal hemodynamics (group B, n = 15, PCWP >15 mm Hg at rest or >18 mm Hg following volume load). For the establishment of the potential role of NO, endomyocardial iNOS gene expression level was measured. Results: Except for PCWP ( P < 0.001) and mean pulmonary artery pressure ( P < 0.001) no differences in age, baseline characteristics, and ejection fraction were observed between both groups, and volume load significantly increased PCWP in both groups (group A: P < 0.001 and group B: P < 0.001) without any change in heart rate. Interestingly, volume load significantly increased CI in group A ( P < 0.001) but not in group B ( P = 0.654), and the Starling curves revealed a higher CI at any given PCWP in group A together with significantly higher iNOS gene expression ( P = 0.009). Conclusions: In HTx, volume load increases FP and unmasks the presence of left ventricular diastolic dysfunction. Interestingly, following saline load group B shows a blunted Starling response, with higher PCWP and lack of CI increase at any given PCWP. The higher iNOS gene expression level in group A suggests a potential role of NO as mediator of diastolic function.